1997
DOI: 10.1292/jvms.59.689
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Commercial Isotonic Fluids Intravenously Administered to Rehydrate Fasted Bullocks.

Abstract: ABSTRACT. Holstein bullocks were used in this study to compare the effectiveness of five commercial parenteral fluids (saline IS, Hartmann's IH, 5%-glucose 5G, Ringers IR, and 1/2 Ringer's and 2.5% glucose combination solutions RG) in correcting the disturbances associated with dehydration induced by fasting for 48 hr. These five commercial fluids (30 ml/kg) were given to bullocks with dehydration induced by fasting for 48 hr. Arterial and venous blood samples were taken before fasting, and at 0, 15, 30, 45, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…The decreased MAP in the those two groups remained at values lower than those at 0 min value (p<0.05). In a similar manner, SAP and DAP in the beagles given 5 or 15 ml/kg-HSS were significantly decreased at 2 min after the initiation of the fluid infusion, The rPV values were calculated from Hb and Ht, using Greenleaf's formulas [7,18]. Level of significance (p<0.05) indicated: a: vs 5 ml/kg ISS, b: vs 2.5 ml/kg HSS and c: vs 5 ml/kg HSS.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The decreased MAP in the those two groups remained at values lower than those at 0 min value (p<0.05). In a similar manner, SAP and DAP in the beagles given 5 or 15 ml/kg-HSS were significantly decreased at 2 min after the initiation of the fluid infusion, The rPV values were calculated from Hb and Ht, using Greenleaf's formulas [7,18]. Level of significance (p<0.05) indicated: a: vs 5 ml/kg ISS, b: vs 2.5 ml/kg HSS and c: vs 5 ml/kg HSS.…”
Section: Resultsmentioning
confidence: 97%
“…Several possibilities concerning the mechanisms of beneficial effects of a HSS intravenous (IV) infusion have been proposed, as follows. One possibility is the expansion of circulating volume [2,3,8,10,13,14,[18][19][20]. A 140 ml infusion of HSS can drew 575 ml and 285 ml of water from interstitial and intracellular fluid compartments, respectively; the expanding plasma volume thus reached 1,000 ml [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some venous blood samples were used to determine the hemoglobin concentration (Hb) and hematocrit value (Ht) with an automatic cell counter (MEK-6248: Nihon Koden). Changes in the relative plasma volume (rPV) were calculated from Hb and Ht, with accepted formulas [5,21]. Relative changes in base excess (rBE) were derived from the following equation: rBE = BE samp -BE pre , where BE samp and BE pre were BE concentrations in each sampling and pre point, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Person et al [14] suggested that hypotonic saline solution with 2.5% dextrose appeared to be the most appropriate solution when moderate dehydration of children had to be corrected immediately by fluid infusion. Our previous study indicated that hypotonic Ringer's solution with 2.5% dextrose (RS) did not change the balance of plasma electrolyte and induced a proper reabsorption rate of glucose in the renal system [15]. Metabolic acidosis is also a common occurrence in calves with diarrhea.…”
mentioning
confidence: 99%